Results and toxicity of chemoradiotherapy in patients with cervical carcinoma - Jakubowicz, Jerzy; Reinfuss, Marian; Blecharz, Paweł; Skotnicki, Piotr; Szatkowski, Wiktor; Krzystek-Małecka, Halina (Contemporary Oncology/Współczesna Onkologia, 2008)
The paper presents a literature review, regarding the chemoradiotherapy outcomes in patients with locally advanced cervical cancer, since the report of the National Cancer Institute in 1999, when this treatment option was first recommended. The authors demonstrated that the alterations in methods of irradiation and chemotherapy and disparities in population and clinical features among groups make the evaluation of treatment outcomes non-comparable. Moreover, differences in therapy results are caused by various treatment methods among centres. Also, the comparison of early and late toxicity between chemoradiotherapy and radiotherapy alone in this group of patients is presented in the paper.